Kepemimpinan Hamba Berdasarkan Markus 10:42-45 dan Implementasinya Bagi Guru Pendidikan Agama Kristen - Vernando Purba; Andrianus Nababan (Institut Agama Kristen Negeri Tarutung, 2023)
A Christian Religious Education Teacher, does not only teach or force people to do God's word. But do it first. A teacher. Christian Religious Education must view that its leadership is the leadership of a servant, and not as a master or boss who only commands. The leadership of Jesus is an example in implementing servant leadership and being a leader who is an example in ministry. Being a Christian Religious Education Teacher who serves, means lowering yourself, taking a place that other people think is inappropriate. For a Christian Religious Education teacher, he should have the principle that his leadership is a leader who serves and not to be served. Just like Jesus who came into the world taking the form of a servant to serve. A Christian Religious Education Teacher has the initiative that is born from within to serve, has a self-sacrificing attitude. Willing to sacrifice means setting aside personal interests for the common good. These things become benchmarks that can be applied by servant leaders.